Nanoscale solid-state quantum computing. - Ardavan, A; Austwick, M; Benjamin, S; Briggs, G; Dennis, T; Ferguson, A; Hasko, D; Kanai, M; Khlobystov, A; Lovett, B; Morley, G; Oliver, R; et al. (2003)
Most experts agree that it is too early to say how quantum computers will eventually be built, and several nanoscale solid-state schemes are being implemented in a range of materials. Nanofabricated quantum dots can be made in designer configurations, with established technology for controlling interactions and for reading out results. Epitaxial quantum dots can be grown in vertical arrays in semiconductors, and ultrafast optical techniques are available for controlling and measuring their excitations. Single-walled carbon nanotubes can be used for molecular self-assembly of endohedral fullerenes, which can embody quantum information in the electron spin. The challenges of individual addressing in such tiny structures could rapidly become intractable with increasing numbers of qubits, but these schemes are amenable to global addressing methods for computation.